Navigating Geographic and Cultural Barriers: Principal Leadership Strategies in Developing Professional Learning Communities in Remote Indonesian Schools - Kasri, Kasri; Andriani, Dwi Estri (Journal of Innovation and Research in Primary Education, 2025)
Professional Learning Communities (PLCs) have emerged as critical frameworks for enhancing teacher professional development and improving educational quality. However, implementation challenges persist, particularly in remote geographical contexts where principals must navigate complex barriers to foster collaborative professional cultures. This qualitative study employed an exploratory case study design across three junior secondary schools in Merauke Regency, Papua Selatan, Indonesia. Data were collected through semi-structured interviews with six participants (three principals and three teachers), document analysis, and direct observations. Data analysis followed Miles, Huberman, and Saldana's three-stage approach, with triangulation ensuring credibility. Three primary themes emerged: principal conceptualizations of PLCs as multifunctional collaborative platforms, implementation challenges including geographic barriers (primary obstacle), limited understanding, senior teacher resistance, technology constraints, and role multiplicity, and strategic responses encompassing flexible scheduling, personalized engagement, senior teacher valorization, technology training, and workload management. Geographic barriers significantly impacted teacher participation due to extensive commuting distances, while principals successfully employed adaptive strategies to overcome contextual obstacles. The findings demonstrate that effective PLC development requires adaptive leadership integrating transformational, situational, and inclusive approaches. The study extends educational leadership theory by highlighting culturally specific PLC dimensions and challenging universal implementation models. Results provide evidence-based strategies for developing PLCs in resource-constrained environments, emphasizing relationship-building and contextual responsiveness over rigid program adherence.